2018
DOI: 10.1590/0103-8478cr20180412
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of heterologous microsatellite primers in Brycon gouldingi

Abstract: Brycon gouldingi is a species of neotropical fish of socioeconomic and environmental importance in the Tocantins-Araguaia Basin. Genetic studies on this species are still limited, making it difficult to evaluate the population structure and genetic diversity in natural and captive stocks. Here, we aimed to evaluate the transferability of heterologous microsatellite primers in B. gouldingi. A total of 30 primers for eight species were evaluated: Brycon hilarii, Brycon opalinus, Brycon cephalus, Brycon orbignyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
5
1
1
Order By: Relevance
“…According to the authors, the Rio Verde population presented satisfactory genetic variability. A B. gouldingi population of the Araguaia River (Souza et al 2018b) had lower Ho (0.157) and He (0.357) than those found for B. falcatus in our study. Our results demonstrate a moderate genetic variability in the B. falcatus population.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…According to the authors, the Rio Verde population presented satisfactory genetic variability. A B. gouldingi population of the Araguaia River (Souza et al 2018b) had lower Ho (0.157) and He (0.357) than those found for B. falcatus in our study. Our results demonstrate a moderate genetic variability in the B. falcatus population.…”
Section: Discussioncontrasting
confidence: 85%
“…The number of alleles per locus in most primers was similar to that found by Castro et al (2017) in cross-amplification of microsatellite markers of B. hilarii and B. opalinus in B. orbignyans; and similar to that found by Souza et al (2018b) in cross-amplification of microsatellite of B. hilarii, B. opalinus and B. orbignyanus in B. goudingi. In a study with natural populations of Prochilodus lineatus, Lopera- Barrero et al (2016b) found a variation of three to six alleles produced by the Par12 locus and three to five alleles produced by the Par80 locus.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In general, primers of species with phylogenetic proximity are used, and generally the primers with the highest reproducibility are those from species belonging to the same genus or family (Carmo, Polo, Silva, & Yazbeck., 2015;Castro et al, 2017;Lima et al, 2008). Some studies have demonstrated the efficiency of cross-amplification in Brazilian native fish species, such as Brycon orbignyanus (Carmo et al, 2015), Brycon gouldingi (Souza et al, 2018a), Leporinus elongatus, Rhamdia quelen (Lopera-Barrero et al, 2016), and Colossoma macropomum (Lima et al, 2008). However, the lack of characterization of specific molecular markers or studies with transferability of microsatellite primers in L. marmoratus limits genetic studies on this species.…”
Section: Introductionmentioning
confidence: 99%